Internalisasi Tata Kelola Administrasi Pemerintahan melalui Praktik Kerja Lapangan di DPRD Kota Bengkulu - Tauhid, Muhammad Ikhsan; Alam, RG Guntur; Wijaya, Ardi (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
Fieldwork Internship is a strategic curricular instrument that bridges the gap between academic theory and the empirical reality of the workplace. This activity aims to analyze the effectiveness of the implementation of Field Work Internship at the Bengkulu City DPRD Secretariat in improving student competency in public administration and legislative mechanisms. Using descriptive qualitative methods with participatory observation and in-depth interviews, this study evaluates student involvement in the management of official documents and government bureaucratic procedures. The outcomes of this activity indicate that student integration into the legislative work environment significantly improves administrative skills, understanding of sectoral regulations, and internalization of professional ethics. These findings confirm that practical experience in state institutions plays a crucial role in shaping students' career readiness, particularly in facing the complex dynamics of the public sector.